Response of seashore paspalum and bermudagrass to topramezone and triclopyr mixtures. (9th June 2021) - Gonçalves, Clebson G.; Brown, Austin M.; Basak, Suma; McElroy, J. Scott
Abstract: Few options are available for controlling bermudagrass invasion of seashore paspalum. Bermudagrass and seashore paspalum tolerance to topramezone, triclopyr, or the combination of these two herbicides were evaluated in both greenhouse and field conditions. Field treatments included two sequential applications of topramezone (15.6 g ai ha −1 ) alone and five rates of topramezone + triclopyr (15.6 + 43.2, 15.6 + 86.3, 15.6 + 172.6, 15.6 + 345.2, or 15.6 g ai ha −1 + 690.4 g ae ha −1 ). Secondary greenhouse treatments included a single application of topramezone (20.8 g ha −1 ) or triclopyr (258.9 g ha −1 ) alone, or in combination at 20.8 + 258.9 or 20.8 + 517.8 g ha −1, respectively. Greenhouse and field results showed that topramezone applications in combination with triclopyr present opposite responses between bermudagrass and seashore paspalum. Topramezone increased bermudagrass injury and decreased seashore paspalum bleaching injury compared to topramezone alone. In field evaluations, topramezone + triclopyr at 15.6 + 690.4 g ha −1 used in sequential applications resulted in >90% injury to bermudagrass, however, injury decreased over time. Furthermore, sequential applications of topramezone + triclopyr at 15.6 + 690.4 g ha −1 resulted in >50% injury to seashore paspalum. Application programs including topramezone plus triclopyr should increase bermudagrass suppression and reduce seashore paspalum injury compared to topramezone alone. However, additional studies are needed because such practices will likely require manipulation of topramezone rate, application timing, application interval, and number of applications in order to maximize bermudagrass control and minimize seashore paspalum injury.